Integrative Analysis of the GRAS Genes From Chinese White Pear (Pyrus bretschneideri): A Critical Role in Leaf Regeneration - Wang, Xinya; Manzoor, Muhammad Aamir; Wang, Mengna; Zhao, Yu; Feng, Xiaofeng; Alam, Pravej; Chi, Xujing; Cai, Yongping (Frontiers in Plant Science, 2022)
GRAS is a transcription regulator factor, which plays an important role in plant growth and development. Previous analyses found that several GRAS functions have been identified, such as axillary bud meristem formation, radial root elongation, gibberellin signaling, light signaling, and abiotic stress. Although the GRAS family has been comprehensively evaluated in several species. However, little finding is on the GRAS transcription factors (TFs) in pear. In this study, 99 PbGRAS were systemically characterized and renamed PbGRAS1 to PbGRAS99 according to their chromosomal localizations. Phylogenetic analysis and structural features revealed that could be classified into eight subfamilies (LISCL, Ls, SHR, HAM, SCL, PAT, SCR, and DELLA). Further analysis of introns/exons and conserved motifs revealed that they are diverse and functionally differentiated in number and structure. Synteny analysis among Pyrus bretschenedri, Prunus mume, Prunus avium, Fragaria vesca and Prunus persica showed that GRAS duplicated regions were more conserved. Dispersed duplication events are the most common mechanism and may play a crucial role in the expansion of the GRAS gene family. In addition, cis-acting elements of the PbGRAS gene were found in promoter regions associated with hormone and environmental stress responses. Notably, the expression pattern detected by qRT-PCR indicated that PbGRAS genes were differentially expressed under gibberellin (GA), abscisic acid (ABA), and auxin (IAA) conditions, which are responsive to abiotic stress. PbGRAS89 and PbGRAS99 were highly expressed at different stages of hormone treatment and may play important role in leaf development. Therefore, we selected PbGRAS89 and PbGRAS99 to clone and construct pCAMBIA1301-PbGRAS89, 99 and transferred them into Arabidopsis thaliana. Finally, observe and compare the changes of overexpressed plants and wild-type plants during regeneration. Through this method to analysis their roles in leaf regeneration of pear. In addition, we also constructed pCAMBIA1305-PbGRAS89, 99, and transferred them into onion cells to determine the subcellular localization. Subcellular localization experiments showed that PbGRAS89 and PbGRAS99 were localized in the nucleus. In summary, the results of this study indicate that PbGRAS89 and PbGRAS99 are mainly responsible for leaf regeneration of pear, which plays a positive role in callus formation and provides rich resources for studying GRAS gene functions.